As per analysis for previous years, it has been observed that students preparing for JEE MAINS find Mathematics out of all the sections to be complex to handle and the majority of them are not able to comprehend the reason behind it. This problem arises especially because these aspirants appearing for the examination are more inclined to have a keen interest in Mathematics due to their ENGINEERING background.
Furthermore, sections such as Mathematics are dominantly based on theories, laws, numerical in comparison to a section of Engineering which is more of fact-based,physics and includes substantial explanations. By using the table given below, you easily and directly access to the topics and respective links of MCQs. Moreover, to make learning smooth and efficient, all the questions come with their supportive solutions to make utilization of time even more productive. Students will be covered for all their studies as the topics are available from basics to even the most advanced. .

**Q1.**The value of lim

_{x→Ï€/4} (2√2-(cosx+sinx )

^{3})/(1-sin2x ), is

Solution

We have, lim

We have, lim

_{x→Ï€/4} (2√2-(cosx+sinx )^{3})/(1-sin2x ) =lim_{x→Ï€/4}(2^{(3/2)}-{(cosx+sinx )^{2}}^{(3/2)})/(2-(1+sin2x)) =lim_{x→Ï€/4}(2^{(3/2)}-(1+sin2x )^{(3/2)})/(2-(1+sin2x)) =lim_{y→2} (y^{(3/2)}-2^{(3/2)})/(y-2), where y=1+sin2x =3/2 (2)^{(3/2-1)}=3/2×√2=3/√2**Q2.**lim

_{x→0}x

^{2}sin Ï€/x, us

Solution

We have, lim

We have, lim

_{x→0}x^{2}sin Ï€/x =0×(A finite oscillating number)=0**Q3.**lim

_{x→0}[(2

^{x}-1)/(√(1+x)-1)] is equal to

Solution

lim

lim

_{x→0}[(2^{x}-1)/(√(1+x)-1)]=lim_{x→0} (2^{x}log_{e}2)/(1/(2√(1+x))) [by L’ Hospital’s rule] =2log_{e} 2=log_{e}4

**Q4.**If lim

_{n→∞} (1-(10)

^{n})/(1+(10)

^{(n+1)})=(-Î±)/10, then the value of Î± is

Solution

lim

lim

_{n→∞} (1-(10)^{n})/(1+(10)^{(n+1)}) =lim_{n→∞} 10^{n}/ 10^{(n+1)}((1/10^{n}-1)/(1/ 10^{(n+1)}+1)) ⇒ -Î±/10=1/10 ((0-1)/(0+1))=-1/10 [given] ⇒ Î±=1**Q5.**The value of lim

_{x→∞} ((x-1)/(x+1))

^{x}, is

Solution

We have, lim

We have, lim

_{x→∞}(1-2/(x+1))^{x}=e^{limx→∞ (-2x)/(x+1)}=e^{-2}**Q6.**lim

_{x→-∞}(3x+√(9x

^{2}-x)) equals

Solution

We have, lim

We have, lim

_{x→-∞}(3x+√(9x^{2}-x)) =lim_{y→∞}(-3y+√(9y^{2}+y)),where y=-x =lim_{y→∞} (-9y^{2}+9y^{2}+y)/((3y+√(9y^{2})+y))=lim_{y→∞} y/(3y+√(9y^{2})+y)=1/(3+3)=1/6**Q7.**lim

_{x→0}e

^{(tanx-ex )}/(tanx-x)=

Solution

We have, lim

We have, lim

_{x→0}(e^{tanx}-e^{x})/(tanx-x) =lim_{x→0} (e^{x}{e^{(tanx-x)}-1})/(tanx-x) =lim_{x→0} e^{x}×lim_{x→0} (e^{(tanx-x)}-1)/(tanx-x) e^{0}×1=1**Q8.**Let f(x)={ (1,when x is rational 0,when x irrational) , then lim

_{x→0} f(x) is

Solution

LHL=lim

LHL=lim

_{x→0-} f(x)=lim_{h→0} f(0-h)=1 [∵(0-h) is rational] RHL=lim_{x→0+ } f(x)=lim_{h→0} f(0+h)=1 [∵(0+h) is rational] Hence, LHL=RHL=1**Q9.**lim

_{x→0} (a

^{x}+a

^{-x}-2)/x

^{2}is equal to

Solution

lim

lim

_{x→0} (a^{x}+a^{-x}-2)/x^{2}=lim_{x→0})(a^{x}loga-a^{-x}loga)/2x [by L’ Hospital’s rule] =lim_{x→0} (a^{x}(log a)^{2}+a^{-x}(log a)^{2})/2 =(loga )^{2}[by L’ Hospital’s rule]**Q10.**If f(x)=2/(x-3),g(x)=(x-3)/(x+4) and h(x)=-(2(2x+1))/(x

^{2}+x-12), then lim

_{x→3}{f(x)+g(x)+h(x)}, is

Solution

We have, f(x)+g(x)+h(x)=(x

We have, f(x)+g(x)+h(x)=(x

^{2}-4x+17-4x-2)/(x^{2}+x-12)=((x-3)(x-5))/((x-3)(x+4)) ∴lim_{x→3}[f(x)+g(x)+h(x) ]=lim_{x→3} ((x-3)(x-5))/((x-3)(x+4))=-2/7